Islamic Political Paradigm: Historical Review, Transformation, and Symbolism - Nur Halimah; Kamilatul Ubudiyah; Rachmad Ramadhan (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Islam as an identity for Muslims originates from the Qur'an and Hadith which has important topics of discussion, one of which is politics. Even though Islam talks about politics, it does not explicitly mention the ideal form of political system. One of the characteristics of Islamic political thought during the time of Rasulullah SAW. and the Khulafa'ur Rasyidin are those which only focus on conquering or expanding territory, integration and consolidation of Islamic political power.In addition, political thought that develops also tends to be a response to the socio-political conditions that occur. This type of research from the point of view of the paradigm is qualitative research. Qualitative research aims to find conceptual meaning as a whole based on facts and sayings and actions. The research method used is library research, namely research activities that are used systematically to collect information, process and conclude data from various kinds of materials in the library. This research is descriptive analytical. Descriptively, this study aims to explain Islamic political thought in the era of the leadership of the Prophet and Khulafaur Rasyidin in Islam and the relationship between religion and the state. The research data obtained were then analyzed and interpreted to obtain adequate meaning